Recent Experiences in Managing Capital Inflows-Cross-Cutting Themes and Possible Policy Framework : Supplementary Information. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This supplement provides further information on some of the issues covered in Recent Experiences in Managing Capital Inflows-Cross-Cutting Themes and Possible Policy Framework that have been highlighted in staff's informal discussions with Directors. These include the role of supply-side factors behind the surge in capital flows and the nature of the framework pertaining to the use of capital flow management measures (CFMs).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Cross-Cutting Theme; Fund; Policy Advice; PP; Theme; United States